2021
DOI: 10.1002/vetr.134
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on the use of lumbosacral epidural analgesia during caesarean section surgery in 182 dogs: Impact on blood pressure, analgesic use and delays

Abstract: Background: We evaluated the use of lumbosacral epidural anaesthesia (LEA) in dogs undergoing caesarean section over 10 years. Methods: Anaesthetic records were reviewed and divided into two treatment groups: LEA and control. Outcome variables identified a priori as potentially affected by LEA were compared between groups. Results are frequency or median (minimum–maximum). Results: Ninety‐five dogs received LEA and 87 did not. LEA consisted of 0.2 (0.1–0.3) ml/kg containing bupivacaine (n = 63), ropivacaine (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…Indeed, when ropivacaine was injected into the thoracic epidural space, the MAP decreased significantly in humans only at a dose of ropivacaine 0.75% but not with ropivacaine 0.375% or 0.2% ( 33 ). In dogs undergoing a cesarean section, the use of lumbosacral epidural analgesia (ropivacaine, bupivacaine or lidocaine) at a maximum volume of 0.3 mL kg −1 did not exacerbate hypotension ( 34 ). In our study, MAP differed between the SC and LS group at 30 min after the injection, but since the MAP was above the set threshold for treatment in both groups, this information might be not clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when ropivacaine was injected into the thoracic epidural space, the MAP decreased significantly in humans only at a dose of ropivacaine 0.75% but not with ropivacaine 0.375% or 0.2% ( 33 ). In dogs undergoing a cesarean section, the use of lumbosacral epidural analgesia (ropivacaine, bupivacaine or lidocaine) at a maximum volume of 0.3 mL kg −1 did not exacerbate hypotension ( 34 ). In our study, MAP differed between the SC and LS group at 30 min after the injection, but since the MAP was above the set threshold for treatment in both groups, this information might be not clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that during cesarean section (CS), hypotension following EA can occur in up to 80% of women (2)(3)(4); similar findings have also been noted in dogs (5)(6)(7)(8)(9)(10). The consequences of low blood pressure affect both, the mother and unborn fetus.…”
Section: Introductionmentioning
confidence: 89%
“…The dogs were healthy, and without any systemic diseases based on routine clinical, hematological, and biochemical examinations. The mean body weight of the females was 14.6 kg (3–46 kg), and the mean age was 4.1 ( 2 8 ) years. Cesarean section was performed independently in this research.…”
Section: Methodsmentioning
confidence: 99%
“…Animal anatomical variability and physicochemical properties of the drug that limit rostral spread and incomplete effects include highly lipophilic drugs, meningovertebral ligaments that cause compartmentalization, increased epidural space pressures, positioning that increases frictional and gravity forces against the injectate, and leakage from the epidural space through intervertebral foramina ). In addition, insufficient dose and inappropriate technique may be contributing factors (Hermanides et al 2012;Martin-Flores et al 2021).…”
Section: Underdosingmentioning
confidence: 99%